Examining the impact of globalization and natural resources on environmental sustainability in G20 countries - Caihua Wang; Hamid Mahmood; Samia Khalid (Scientific Reports)
Abstract The G20 countries are responsible for around 75% of the world’s greenhouse gas (GHG) emissions, including the use of natural resources. In this regard, the role of globalization in achieving environmental sustainability is a relatively new topic of concern. As a result, the present study considers how globalization and natural resources affect GHG emissions, as well as the roles that renewable energy consumption and urbanization play in the G20 countries between 1990 and 2020. Moreover, this research utilizes advanced panel data estimation methods to assess these interrelationships, like CUP-FM and CUP-BC methods. The study finds that globalization and natural resource use contribute to increased GHG emissions, with a more pronounced effect in high-income countries because most of the countries have extended carbon taxes or emissions trading systems in the last few years. Conversely, the adoption of renewable energy is associated with a reduction in emissions, underscoring the importance of transitioning to cleaner energy sources. Urbanization trends also correlate positively with GHG emissions, highlighting the environmental impact of rapid urban growth, particularly in middle-income countries. These results underscore the need for targeted policy interventions. High-income countries should intensify efforts to reduce emissions through renewable energy and stricter regulations on resource consumption. While, middle-income countries require support to manage urbanization and adopt sustainable practices. This study provides crucial insights into the complex dynamics of globalization, resource use, and sustainability, offering valuable guidance for policymakers and researchers engaged in environmental management and climate change mitigation.